Unfolding the subjectivity of foreign language enjoyment in online classes: A Q methodology study - Athip Thumvichit (2022)
The effects of positive emotions on learners’ achievement and well-being highlight the need to delve into foreign language enjoyment (FLE) in different contexts and from different perspectives. This study uses Q methodology to explore English as a Foreign Language (EFL) learners’ subjective perspectives regarding FLE during a period of online learning necessitated by the COVID-19 pandemic. A Q sort of 47 statements was administered to 41 Thai tertiary-level students. Data were analysed using principal component analysis and varimax rotation to extract common patterns across the Q sorts. The results reveal three distinct viewpoints. Viewpoint A focuses significantly on teachers’ characteristics and practices, whereas Viewpoints B and C lean towards learner autonomy and social experiences, respectively. Also found is that the emergence of these factors came at the expense of other factors; for example, peer-to-peer interactions were sacrificed as classes were oriented towards independent learning. The heterogeneity of EFL learners on what constitutes enjoyment in online learning reinforces the idea that online instruction should be delivered and organised in such a way as to emphasise interconnected factors to secure learning enjoyment and achievement.